Mother’s Knowledge, Attitude and Practices and its Influence toward Nutritional Status of Children in Terengganu - Juhari, Nur Husna Syahirah; Suan, Wee Bee (Jurnal Gizi dan Pangan, 2024)
This cross-sectional study aimed to identify the nutritional status, Knowledge, Attitude and Practice (KAP) regarding stunting among mothers and its relationship with stunting among children below two years old in Terengganu. A total of 330 mother-child pairs from Terengganu were recruited through purposive sampling. Anthropometric measurement comprised weight and height. Information on socio–demographic, and a validated questionnaire on knowledge, attitude and practice of stunting were selfreported. Chi-square test was applied in this study with p<0.05 considered significant outcome. The majority (61.2%) of the mothers aged 30−39 years old, with tertiary educational level (51.5%) and in the low income group (86.4%). The prevalence of stunting, wasting and underweight was 25.2%, 9.4% and 14.2% respectively for the children below two years old in Terengganu. KAP analysis revealed that 44.5% of mothers had moderate level of knowledge, while 68.8% and 92.7% had good level of attitude and practice, respectively. A significant association (p<0.05) was found between knowledge of mothers with stunting among the children, while no significant association between attitudes and practice with stunting. The present study found that mothers’ knowledge significantly impacted their child’s growth status in relation to stunting. Future intervention programmes should incorporate nutrition education focusing on mothers’ knowledge to prevent stunting among children.